Comments on the typification of two names in Bauhinia, now under Phanera (Leguminosae: Cercidoideae) - Bandyopadhyay, Subir; Krishna, Gopal; Kumar, Anand (Thai Forest Bulletin (Botany), 2021)
A lectotype is designated here for Bauhinia cardinalis, the basionym of Phanera cardinalis and a second-step lectotype is designated here for B. penicilliloba, the basionym of P. penicilliloba.